Dynamic scaffolds for neuronal signaling: in silico analysis of the TANC protein family - Alessandra Gasparini (Nature Portfolio, 2017)
Abstract The emergence of genes implicated across multiple comorbid neurologic disorders allows to identify shared underlying molecular pathways. Recently, investigation of patients with diverse neurologic disorders found TANC1 and TANC2 as possible candidate disease genes. While the TANC proteins have been reported as postsynaptic scaffolds influencing synaptic spines and excitatory synapse strength, their molecular functions remain unknown. Here, we conducted a comprehensive in silico analysis of the TANC protein family to characterize their molecular role and understand possible neurobiological consequences of their disruption. The known Ankyrin and tetratricopeptide repeat (TPR) domains have been modeled. The newly predicted N-terminal ATPase domain may function as a regulated molecular switch for downstream signaling. Several putative conserved protein binding motifs allowed to extend the TANC interaction network. Interestingly, we highlighted connections with different signaling pathways converging to modulate neuronal activity. Beyond a known role for TANC family members in the glutamate receptor pathway, they seem linked to planar cell polarity signaling, Hippo pathway, and cilium assembly. This suggests an important role in neuron projection, extension and differentiation.